Mauritius : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper and Statistical Appendix provide background information and analytical support for key policy issues discussed in the 2004 Article IV Consultation discussions with Mauritius. The impact of the erosion of trade preferences on exports, growth, and employment is assessed under two scenarios-a moderate and an extreme scenario. To quantify the adverse impact of trade liberalization, the paper estimates various elasticities of GDP growth to exports, and unemployment to growth. The paper also analyzes the labor market institutions and low-skilled employment in Mauritius.